2017
DOI: 10.1155/2017/6495861
|View full text |Cite
|
Sign up to set email alerts
|

Time Coefficient Estimation for Hourly Origin-Destination Demand from Observed Link Flow Based on Semidynamic Traffic Assignment

Abstract: Day-long origin-destination (OD) demand estimation for transportation forecasting is advantageous in terms of accuracy and reliability because it is not affected by hourly variations in the OD distribution. In this paper, we propose a method to estimate the time coefficient of day-long OD demand to estimate hourly OD demand and to predict hourly traffic for urban transportation planning of a large-scale road network that lacks discrete-time rich traffic data. The model proposed estimates the time coefficients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…The stochastic failure of the road section is used to determine the capacity of the road system during the flash flood. The hourly travel demand, taken from OD matrices of both passenger cars and trucks, are obtained from Fujita et al ( 36 , 37 ); they were calibrated from observed link traffic counts. Simultaneous failures of road segments are generated using Monte Carlo analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The stochastic failure of the road section is used to determine the capacity of the road system during the flash flood. The hourly travel demand, taken from OD matrices of both passenger cars and trucks, are obtained from Fujita et al ( 36 , 37 ); they were calibrated from observed link traffic counts. Simultaneous failures of road segments are generated using Monte Carlo analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Fujita et al have proposed a model for estimation of these time coefficients using links volume counting and Semidynamic Traffic Assignment [2]. In that study, a model has been developed that justifies the 24-hour time coefficients under a given day-long OD demand by minimizing the least square error between hourly observed link flow and estimated link flow But this research is useful for operational analysis, not for strategic planning because the analyst does not have access to link volumes in horizon year.…”
Section: E Dtc Model As a Tool For Predicting Peak Hours Pattern In Long-term Planning (As A Time Of Day Modelmentioning
confidence: 99%
“…We did not nd appropriate DTC model that is useful on four-step strategic planning. e proposed model in the study of Fujita et al [2] is useful for operational analysis, not for strategic planning because the analyst does not have access to link volumes in horizon year. Ettema [29] suggested that sociodemographic variables be incorporated within the DTC model.…”
Section: Remarks and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Toledo and Kolechkina [14] presented the methods based on use of linear approximations of the assignment matrix in the optimization iterations. Fujita et al [15] proposed an OD modification approach formulated as a static user-equilibrium assignment with elastic demand, based on the residual demand at the end of each period. Applying the model to large-scale road network demonstrates that it efficiently improves estimation accuracy because the 24-hour time coefficients of survey data are slightly biased and may be modified properly.…”
Section: Introductionmentioning
confidence: 99%